The Biological Diversity of Fruit Flies (Diptera: Drosophilidae) in Russia: A Description of a Set of Own and Published Data and a Complete List of Species - Nikolai G. Gornostaev; Alexander B. Ruchin; Mikhail N. Esin; Evgeniy A. Lobachev; Irina G. Esina (Diversity)
Drosophilidae is a relatively small family within Diptera. However, species of this family occupy a wide range of ecological niches and are frequently found in synanthropic habitats. Additionally, some species are known agricultural pests. The dataset is based on collections of Drosophilidae from eleven regions of Russia. The dataset was uploaded to the GBIF platform in 2024. Published sources specifying exact localities and collection dates were also used. The database includes records dating back to 1867, with the majority of specimens collected by the authors between 2001 and 2024. Collection methods included net sweeping and bait trapping. The dataset contains 2830 occurrence records, with a total of 51,006 specimens of Drosophilidae studied. It includes data on 108 species from two subfamilies, covering 49 regions of Russia. Considering additional published sources, 188 species of Drosophilidae are currently known from Russia, with a complete species list provided. Among the most abundant species in the dataset, 10 species are represented by more than 1000 specimens: Drosophila obscura, Scaptodrosophila rufifrons, Drosophila melanogaster, Drosophila phalerata, Drosophila transversa, Drosophila kuntzei, Drosophila histrio, Drosophila testacea, Phortica semivirgo, and Drosophila immigrans. Conversely, 39 species are represented by fewer than 10 specimens in the dataset. Regarding ecological groupings, the most dominant groups are xylosaprobionts (39 species, 40.6%) and mycophages (30 species, 31.3%). Notably, in 2017, the quarantine pest Drosophila suzukii was detected in the European part of Russia. The current knowledge of the Drosophilidae fauna in Russia remains insufficient. Of the 15 regions, only one or two localities are represented in the dataset. The distribution limits and range boundaries of many species remain unknown. Moreover, the local faunas of more than half of Russia’s regions remain unexplored.